A comunicação entre líderes e liderados e sua relação com o comprometimento organizacional - Fernandes, Luciane (Universidade do Vale do Rio dos Sinos, 2020)
The present thesis aims to analyze how the communication process takes place between formal leaders and their followers and their relationship with the organizational commitment of the employees of the Federal Institute of Science and Technology Education of Rio Grande do Sul – Porto Alegre campus (Brazil), identify the processes communication networks, describe the networks, flows and barriers in the management of communication, assess the perception of formal and led leaders and offer suggestions for actions with a view to optimizing communication with regard to organizational commitment. After presenting the theoretical foundation, the methodology adopts the case study, whose research subjects were the formal leaders and their followers. When analyzing the data obtained, it is possible to identify that leaders consider communication to be very important for the performance of functions in the institutional environment, but they are not fully met in the management action plan. It was identified that most of the followers perceive some barriers in communication between the leaders. The predominant organizational commitment is in the affective and instrumental dimension, which promotes engagement and commitment to institutional actions and projects. It is concluded that leaders and subordinates verify the importance of communication in the institutional environment and are willing to contribute to the construction of an environment more and more conducive to knowledge.
Keywords: Gestão; Comunicação; Comprometimento; Educação; Management; Communication; Commitment; Education; ACCNPQ::Ciências Humanas::Educação